Wizerunek wschodnioeuropejskiego Żyda w literaturze i kulturze. Paradoksy i sprzeczności: The cultural self-image of the East European Jew. Paradoxes and contradictions - Zając, Marta (Przegląd Wschodnioeuropejski, 2020)
In my paper I tackle the issue of the cultural self-image of the East European Jew. I provide a critical analysis of a number of texts, of different kinds and bents – confessional, literary, historical, political – to demonstrate the paradoxes and contradictions of Jewish identity. Noticing the bi-polar paths of Jewish self-interpretation (as exemplified, for instance, by Heschel and Szahak), neither free from the subjective and emotional trends, I argue for the truth closer to those views which acknowledge the religious specificity of the Jewish nation as the chosen people. Regardless of multiple contexts worth considering and at work, the essence of Jewishness dwells in the religious feeling.